The Self-Esteem of Generation Z As Leaders: A Study on The Student Council Board for the 2022/2023 School Year at SMA 1 Rejang Lebong - Ristianti, Dina Hajja (Graduate Program Magister Manajemen Pendidikan, 2023)
Self-esteem or good self-esteem is important for a leader. This study aims to determine the self-esteem of the student council board of SMA N 1 Rejang Lebong for the 2022/2023 period who is Generation Z. This study was conducted by providing a self-esteem instrument consisting of 40 questions used to reveal the level of valuable or worthless self-assessment seen in general, personal and social. After being given, the instrument is processed manually which begins with checking, sorting answer sheets, correcting according to norms, and printing results individually or in groups. The results showed that the self-esteem of the student council board of SMA N 1 Rejang Lebong for the 2022/2023 period was included in the medium category as much as 64.8%. This shows that the self-esteem of student council administrators must still be strengthened through leadership development, such as internships, training, or mentorship. They also need to strengthen their self-belief, learn from experiences, and seek support from people who trust and support them.